Kecukupan Ruang Terbuka Hijau (RTH) Publik dalam Menyerap Emisi Karbondioksida (CO2) dari Kegiatan Transportasi di Kecamatan Bukit Raya Pekanbaru - Ayu Putri Permata MS; Yogi Septian Malik (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Green Open Space (GOS) is one of the efforts to deal with increasing GHG emissions because it has the ability to absorb CO2 emissions. Development Area IV Pekanbaru is one of the Development Areas that has the potential to produce carbon dioxide (CO2) emissions, specifically in Bukit Raya Pekanbaru District. This research was conducted to determine the number of motorized vehicles and the value of CO2 emissions produced each day, as well as the value of the capacity of GOS to absorb CO2 emissions from transportation activities in Bukit Raya Pekanbaru District. The method used is recording traffic activities to calculate the amount of CO2 emissions and calculating all public green open spaces with vegetation cover in the form of grasslands and trees with a diameter of ≥ 20 cm, as well as calculating the percentage of green open space absorption capacity. The research results obtained were that the value of CO2 emissions from transportation in Bukit Raya Pekanbaru District was 67,007,898 tons of CO2/year. Meanwhile, the capacity to absorb CO2 by public green open spaces is only 1,992.32 tons of CO2/year. The results show that public green open space in Bukit Raya Pekanbaru District in terms of absorbing CO2 emissions from transportation is still insufficient with a percentage of only 2.97%.